256 Gb/s Four-Channel SDM-Based PAM4 FSO-UWOC Convergent System - Wen-Shing Tsai; Chung-Yi Li; Hai-Han Lu; Yi-Feng Lu; Shi-Cheng Tu; Yong-Cheng Huang (IEEE Photonics Journal, 2019)
Given the rising demand for free-space with underwater environmental monitoring, calamity precaution, and developed industry applications, a free-space optical (FSO)–underwater wireless optical communication (UWOC) convergence is constructed to be an attractive architecture for affording a high transmission capacity. A 256-Gb/s four-channel space-division-multiplexing (SDM)-based four-level pulse-amplitude modulation (PAM4) FSO-UWOC convergent system that exploits two-stage injection-locked red-light vertical-cavity surface-emitting laser transmitters is, thus, offered and practically demonstrated. With a four-channel SDM scheme and PAM4 modulation, the total transmission capacity is drastically enhanced to 256 Gb/s. To the best of our understanding, this architecture is the leading one to build a high-speed 256 Gb/s FSO-UWOC convergent system with competent performances. It directs an approach to expedite extensive applications in the integration of high-speed free-space with underwater links.